IbeR Facilitates Stress-Resistance, Invasion and Pathogenicity of Avian Pathogenic Escherichia coli - Wang, Shaohui (Public Library of Science, 2015)

(untitled) (PLoS One)
Systemic infections by avian pathogenic Escherichia coli (APEC) are economically devastating to poultry industries worldwide. IbeR, located on genomic island GimA, was shown to serve as an RpoS-like regulator in rpoS gene mutation neonatal meningitis E. coli (NMEC) RS218. However, the role of IbeR in pathogenicity of APEC carrying active RpoS has not yet been investigated. We showed that the APEC IbeR could elicit antibodies in infected ducks, suggesting that IbeR might be involved in APEC pathogenicity. To investigate the function of IbeR in APEC pathogenesis, mutant and complementation strains were constructed and characterized. Inactivation of ibeR led to attenuated virulence and reduced invasion capacity towards DF-1 cells, brains and cerebrospinal fluid (CSF) in vitro and in vivo. Bactericidal assays demonstrated that the mutant strain had impaired resistance to environmental stress and specific pathogen-free (SPF) chicken serum. These virulence-related phenotypes were restored by genetic complementation. Quantitative real-time reverse transcription PCR revealed that IbeR controlled expression of stress-resistance genes and virulence genes, which might led to the associated virulence phenotype.